2015
DOI: 10.15414/jmbfs.2015.5.1.64-67
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Efficiency of Resveratrol on Oxidative Stress-Induced Damage in Bovine Spermatozoa

Abstract: Substantial reports suggest that biologically active compounds isolated from natural sources may offer protection to semen against the incidence of free radical producers, improvement of semen quality, prevention of cryodamage and DNA fragmentation, as well as a general promotion of spermatozoa metabolism. This study was therefore designed to assess the impact of resveratrol (RES), a natural polyphenol and phytoalexin with potential antiviral, anti-inflammatory and antioxidant properties on bovine spermatozoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…At 100 μmol/L RES, the motility was absent in all assessed samples, whereas the progressive motility reached its maximum at 6 and 15 μmol/L of RES. Talking in favor of our data, our previous observations (Tvrdá et al, 2015a; did suggest protective effects of RES on bovine sperm motion characteristics, when incubated over a period of 24 h or in the presence of a potent prooxidant, although we must agree that in case of a broader concentration range, RES may act dose dependently as either a stimulant at low doses or as an inhibitor at high doses. This controversy was furthermore assessed by Tvrdá et al (2015b) revealing that 100 and 200 μmol/L RES did not per se exhibit lethal effects on the bovine spermatozoa viability, however its presence suppressed all sperm activity parameters.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…At 100 μmol/L RES, the motility was absent in all assessed samples, whereas the progressive motility reached its maximum at 6 and 15 μmol/L of RES. Talking in favor of our data, our previous observations (Tvrdá et al, 2015a; did suggest protective effects of RES on bovine sperm motion characteristics, when incubated over a period of 24 h or in the presence of a potent prooxidant, although we must agree that in case of a broader concentration range, RES may act dose dependently as either a stimulant at low doses or as an inhibitor at high doses. This controversy was furthermore assessed by Tvrdá et al (2015b) revealing that 100 and 200 μmol/L RES did not per se exhibit lethal effects on the bovine spermatozoa viability, however its presence suppressed all sperm activity parameters.…”
Section: Discussionsupporting
confidence: 41%
“…At the same time, RES has been shown to be a potent antioxidant, based on its ability to modulate the expression and activity of a multitude of antioxidant enzymes (Khan et al, 2013) and to inhibit lipid peroxidation (LPO) (Tadolini et al, 2000). A number of studies have shown that RES acts as a direct ROS quencher (Pandey and Rizvi, 2011) as well as a metal-chelating agent preventing the Fenton reaction (Tvrdá et al, 2015a). With regards to male reproductive function, previous reports have revealed that RES stimulates and protects rabbit and murine spermatocytes and spermatozoa against LPO (Revel et al, 2001;Shi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could preserve the fertilization potential of male reproductive cells (Tvrdá, Kováčik, Tušimová, Massányi, & Lukáč, 2015). In human spermatozoa, its ability to slow down the deleterious effects of in vitro‐associated free radical production has been described (Tvrdá, Kováčik, Tušimová, Lukáč, et al., 2015). Although in this study a reduction in ROS production of the freezing extender was evidenced by the addition of 30 and 50 μM of resveratrol and a ROS reduction in frozen–thawed semen with 20 μM of resveratrol, this did not translate into beneficial effects on sperm conservation.…”
Section: Discussionmentioning
confidence: 99%
“…These bioactive compounds have antibacterial, anti‐inflammatory, anti‐oxidant, anti‐fungal, and anti‐hypoglycemic properties [32,33] . The sage oil extract has a potentially positive effect on male reproductive functions [34,35] . It has been screened as effective against brain and nervous disorders, cardiovascular diseases, and various infections (such as dental abscesses, throat infections, and mouth ulcers) and is claimed to be beneficial to diabetic patients [36] .…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] The sage oil extract has a potentially positive effect on male reproductive functions. [34,35] It has been screened as effective against brain and nervous disorders, cardiovascular diseases, and various infections (such as dental abscesses, throat infections, and mouth ulcers) and is claimed to be beneficial to diabetic patients. [36] The sage oil extract reportedly contains different terpenoids, for instance, 12-O-methylcarnosic, 20-hydroxyferruginol, α-linolenic acid, oleanolic acid, and viridiflorol.…”
Section: Introductionmentioning
confidence: 99%